(untitled) (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
Starting from the postulate that the teaching of French in a FLE context, from both a linguistic and ethical perspective, since the turn of the 21st century, is called upon to pay increased attention to the concept of variation, this reflection fits into the theoretical framework established by sociolinguistics (cf. Gadet (1997) ; Calvet (2017)) and by the study of regionalisms in the Antilles (cf. Thibault (2012)) and aims to identify the forms and challenges of diatopic variation, thus substituting for the notion of the uniqueness of the French language, that of plurality, inclusive and reflexive. The aim is to propose strategies that facilitate the analysis of the morpho-lexical field of a literary corpus rich in metalinguistic echoes, extracted from the second volume of the autofiction Une enfance créole by writer Patrick Chamoiseau, entitled Chemin-d’école, published in 1994. To this end, after identifying specialized lexicographic tools available online, brief lexicographic articles inserted within tables will be presented, allowing observations to be made on the nature of the identified neologisms. It will also be a matter of bringing out a complex literariness, capable of sensitizing learners to central issues mirrored by the text, namely the inherent tensions in a diglossic context that are crystallized, if not surpassed, through literary writing.